The Influence of Life Experiences and Beauty Privilege on Self-Confidence Through Self-Efficacy Among Muslim Students - Putri, Endah Karmila; Khilmiyah, Akif (Jurnal Paedagogy, 2025)
This study aims to examine how the life experiences and self-efficacy of Muslim students affect their sense of self-confidence. The study adopts a quantitative approach, involving 251 Muslim students from various universities in Indonesia as respondents. An online survey was conducted to collect data, focusing on life experiences, beauty privilege, self-efficacy, and self-confidence). Structural Equation Modeling (SEM) techniques were used to analyze the relationships between variables. The results revealed that beauty privilege and life experiences significantly enhance self-confidence, with self-efficacy serving as a mediating factor. For Muslim students, life experiences have a greater impact on self-efficacy and self-confidence compared to beauty privilege. This study suggests enhancing self-efficacy to help Muslim students improve their self-confidence, considering their diverse life experiences and perceptions of attractiveness.